2022
DOI: 10.3390/molecules27041289
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Regulators of Pancreatic Cancer Cell Sensitivity to Oxaliplatin and Cisplatin

Abstract: The chemoresistance of tumor cells is one of the most urgent challenges in modern oncology and in pancreatic cancer, in which this problem is the most prominent. Therefore, the identification of new chemosensitizing co-targets may be a path toward increasing chemotherapy efficacy. In this work, we performed high-performance in vitro knockout CRISPR/Cas9 screening to find potential regulators of the sensitivity of pancreatic cancer. For this purpose, MIA PaCa-2 cells transduced with two sgRNA libraries (“cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Moreover, the NADH dehydrogenase complex, which is one of the key enzymes involved in oxidative phosphorylation and cellular respiration and a key regulator of NAD+/NADH ratio, impacts sensitivity to platinum drugs. Notably, it has been reported that the knockout of NADH dehydrogenase complex subunit genes results in decreased sensitivity to oxaliplatin in pancreatic cells [ 64 ]. In the present study, an increase in the NADH dehydrogenase complex subunit was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the NADH dehydrogenase complex, which is one of the key enzymes involved in oxidative phosphorylation and cellular respiration and a key regulator of NAD+/NADH ratio, impacts sensitivity to platinum drugs. Notably, it has been reported that the knockout of NADH dehydrogenase complex subunit genes results in decreased sensitivity to oxaliplatin in pancreatic cells [ 64 ]. In the present study, an increase in the NADH dehydrogenase complex subunit was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TAGLN2 also shows a higher expression in PC cells than in normal corresponding cells, as previously reported [ 46 ]. Furthermore, the knock-out of FCHO2 increased chemosensitivity in PC MIA-PaCa2 cells in another study [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-containing anti-neoplastic drugs, including oxaliplatin and cisplatin, have been used extensively to treat several cancers. [256][257][258] These drugs work by interfering with the DNA replication process in tumor cells, leading to their death. [259][260][261] However, the effectiveness of these drugs relies on the generation of reactive oxygen species (ROS), which cause oxidative injury to tumor cells.…”
Section: Pharmacomicrobiomics Of Ivdr In Human Diseases Pharmacomicro...mentioning
confidence: 99%